Avaliação das espécies espontâneas na implantação pasto do panicum maximum Cv. aruana no semiárido - Oliveira, Leydiane Bezerra de (2017)
The objective of this study was to evaluate the forage mass of spontaneous species in a pasture of Panicum maximum cv. Aruana in the establishment phase, characterizing the species with cytogenetics and botanical identification. The experiment was carried out in the experimental area of the Paraíba State Agricultural Company (EMEPA) located in Tacima-PB in an area of 0.24 hectares of pasture cultivated with aruana grass. The spontaneous plants were collected between April and August of 2015. The design was in randomized blocks, four blocks that were defined according to the heterogeneity of the area with four experimental treatments that were the four seasons of collection: rainy season, rainy season / Dry, dry and dry / rainy, where the collections occurred from April 2015 to February 2016. 47 spontaneous species were identified in 36 genera and 21 families. The families with the highest number of species were: Fabaceae with nine, Poaceae with five, Malvaceae with four species. The forage mass of the aruana grass was lower in the rainy period of 2015 with 199.61 kg ha-1, the rainy / dry (1299,73 kg ha-1), dry (1519,49 kg ha-1) and Dry / rainy (1183.12 kg ha-1) did not differ from each other. The forage mass of the spontaneous species presented the highest value in the rainy / dry transition period (2512.66 kg ha-1), followed by rainy (1505.47 kg ha-1) and dry / rainy (1051,32 kg Ha-1), while in the dry period there was a decrease (235.62 kg ha-1). The species Panicum maximum cv. Aruana and Herissantia crispa presented the highest frequency in the area with 17.99%, and Centrosema pubescens with the third highest frequency (8.43%). Chromosome counts were made of eleven species, of which four are unpublished. It is concluded that the Fabaceae family obtained a high representativeness of individuals in the area together with the families Poaceae and Malvaceae. The aruana grass presents characteristics of a promising grass for the semiarid regions. It has good reestablishment of its leaf area, seed production for resemeadura and good resistance to drought. The species that presented more than 15% in the area were H. crispa and P. maximum cv. Aruana, which demonstrates their dominance in the area.